Prevalence and Associated Factors of Overweight and Obesity among Adult Gondar Town Residents, North West Ethiopia - Mekonnen, Derese Mekonnen1; Kebede, Yigzaw; Mokonnen, Solomon Mokonnen3 (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2020)
During the last few decades the prevalence of overweight or obesity has been growing at an alarming rate in both the developed and the developing countries at all age level. Overweight and obesity are found to be the leading risk factors contributing for the development of various cardiovascular diseases such as hypertension, type-2 diabetes mellitus, and stroke. It also accounts for some types of cancers like colorectal, breast and endometrial (1-4). However few studies were conducted so far on adults in Gondar town.The main purpose of this study is to assess the prevalence of overweight or obesity and abdominal obesity and to identify associated factors among adults 18 years and older in Gondar town, North West Ethiopia. Community based cross-sectional study conducted from March 18 up to March 27,2014 in Gondar town on 968 study participant. Data gathered using WHO STEP wise instrument using multistage sampling method. Anthropometric measurements such as height, weight and waist circumference measured from study participant using international standard of anthropometric assessment guideline. The prevalence of overweight or obesity and abdominal obesity were assessed using WHO cut off points. Bivariate and multivariate logistic regression models were fitted to see the association between the response and predictor variables and p-value less than 0.05 used as cut point for statically significance. The prevalence of overweight or obesity in the study population was 17.56% [95%CI: 15.56, 19.96], in men 12.69% [95%CI: 9.36, 16.02] and in women 20.79% [95%CI: 17.49, 24.09]. The prevalence of abdominal obesity in the study population was 36.36% [95%CI: 33.33, 39.40], 8.55% [95%CI: 5.75, 11.35] in men and 54.81% [95%CI: 50.76, 58.86] in women. The factors significantly associated with overweight or obesity were sex, age, number of children, wealth index, and eating while watching television. Variables sex, age, wealth index, walking or bicycling were significantly associated with abdominal obesity. The prevalence of overweight or obesity among adult Gondar town residents was high as compared to Ethiopian Demographic and Health Survey reports. The proportion of abdominal obesity in the town was also high. Prevention strategies should be formulated to increase physical activity level and improve dietary habit of the community.